2015
DOI: 10.1038/srep16073
|View full text |Cite
|
Sign up to set email alerts
|

Life history and dynamics of a platypus (Ornithorhynchus anatinus) population: four decades of mark-recapture surveys

Abstract: Knowledge of the life-history and population dynamics of Australia’s iconic and evolutionarily distinct platypus (Ornithorhynchus anatinus) remains poor. We marked-recaptured 812 unique platypuses (total 1,622 captures), over four decades (1973–2014) in the Shoalhaven River, Australia. Strong sex-age differences were observed in life-history, including morphology and longevity. Apparent survival of adult females (Φ = 0.76) were higher than adult males (Φ = 0.57), as in juveniles: females Φ = 0.27, males Φ = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…These observations are consistent with an underlying pattern of limited dispersal of (at least some) relatives. This is somewhat surprising given that previous studies using mark-recapture approaches in the Shoalhaven River ( Grant 2004 ; Bino et al. 2015 ) and other streams ( Serena and Williams 2012 ; Serena et al.…”
Section: Discussionmentioning
confidence: 91%
“…These observations are consistent with an underlying pattern of limited dispersal of (at least some) relatives. This is somewhat surprising given that previous studies using mark-recapture approaches in the Shoalhaven River ( Grant 2004 ; Bino et al. 2015 ) and other streams ( Serena and Williams 2012 ; Serena et al.…”
Section: Discussionmentioning
confidence: 91%
“…Fyke nets (checked every 2–4 h and allowing unimpeded access to air) are effective in small streams, although capture rates may vary substantially by age, sex, and season, and may also be affected by learned avoidance (Serena and Williams 2012b; Griffiths et al 2013). Mark–recapture methods that take into account detection probabilities can produce robust estimates of population size (Bino et al 2015). Environmental DNA (Ficetola et al 2008; Lugg et al 2018) is now used to detect the presence of platypuses and visual survey techniques provide useful information for assessing and monitoring population activity and relative abundance (Easton et al 2008).…”
Section: Researching the Platypusmentioning
confidence: 99%
“…Platypuses are sexually dimorphic, with males approximately 40% heavier and 15% longer than females (Burrell 1927; Temple-Smith 1973; Furlan et al 2012; Bino et al 2015), suggesting that males probably compete for territory, females, and other resources (Brown et al 2013). There is a clinal increase in size from north Queensland (~700–1,100 g) to Tasmania (1,200–3,000 g—Connolly et al 1998; Kolomyjec 2010; Gust and Griffiths 2011; Furlan et al 2012; Bino et al 2015). However, at finer geographical scales, size variation is confounded by inconsistencies, suggesting involvement of other environmental factors (Kolomyjec 2010; Furlan et al 2012).…”
Section: Life Historymentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with an underlying pattern of limited dispersal of (at least some) relatives. This is somewhat surprising given that previous studies using mark-recapture approaches in the Shoalhaven River (Grant, 2004b;Bino and Grant, 2015) and other streams (Serena, 2012;Serena et al, 2014) have reported the dispersal of a high proportion of juveniles, especially males, few recaptures of adult males, and the continued capture of unmarked males and females. Of all the pairs of relatives we sampled at the same site, most were female-female or male-female, and not male-male (there are only three male-male relative pairs in Table S4), which is consistent with male-biased dispersal.…”
Section: Discussionmentioning
confidence: 88%